Precocious centriole disengagement and centrosome fragmentation induced by mitotic delay - Menuka Karki (Nature Portfolio, 2017)
The spindle assembly checkpoint delays mitotic progression until sister chromatids are bi-oriented. Here the authors show that moderate delays in mitotic progression induce centrosome fragmentation and centriole disengagement and that spindle bipolarity is ensured by HSET-mediated spindle pole clustering.